2013
DOI: 10.1159/000349907
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Arousal Deficits in Addicted Gamers Differ Based on Preferred Game Genre

Abstract: Background/Aims: There has been significant discussion surrounding the psychopathology of excessive gaming and whether it constitutes an addiction. The current study investigated physiological and subjective levels of arousal in gamers of two genres and the relationship between sensation seeking and gaming addiction. Methods: Heart rate (HR), blood pressure (BP) and skin conductance were recorded at baseline, during gaming for 15 min and after gaming in 30 massively multiplayer online role-playing game (MMORPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 106 publications
(74 reference statements)
0
6
0
2
Order By: Relevance
“…While the scale used in this study was developed on MMORPGs, it has previously been validated on FPS gamers. 44 Furthermore, the previous study used a single item to represent impulsivity, 33 whereas the BIS-11 used in the this sample is a 30-item, well-established psychometric measure of trait impulsivity. This is also the first study to include laboratory measures of impulsivity in FPS gamers.…”
Section: Discussionmentioning
confidence: 99%
“…While the scale used in this study was developed on MMORPGs, it has previously been validated on FPS gamers. 44 Furthermore, the previous study used a single item to represent impulsivity, 33 whereas the BIS-11 used in the this sample is a 30-item, well-established psychometric measure of trait impulsivity. This is also the first study to include laboratory measures of impulsivity in FPS gamers.…”
Section: Discussionmentioning
confidence: 99%
“…It would suggest that the inter-hemispheric insula FC was involved not only in substance use disorder but also in IGD. Playing online games could bring about a hedonistic experience with a physical hyper-arousal reaction, particularly in first-person shot games [40] . As the insula plays a central role in conscious interoception and emotional feeling, it represented the interoceptive stimuli during the hedonic experience and recalled this experience from memory [39] .…”
Section: The Functional Connection Of the Insulamentioning
confidence: 99%
“…Second, instead of measuring physiological data during the gaming period, physiological arousal after the games and during the Vienna task should be measured in future studies of this sort, which would be useful to see how risky and neutral driving game exposure continues to affect gamers after the game has finished. Metcalf and Pammer's42 study explored the physiological changes before, during and after gaming, and indicated that physiological factors were linked and variable among gamer and gaming type. Physiological changes before, during and after gaming could be compared, which would help in analysing the effect of racing games on risk-taking.…”
Section: Discussionmentioning
confidence: 99%